Use of alternative-complementary-medicine (CAM) in Calabrian children - Dolceamore Teresa Rita; Altomare Federica; Zurlo Francesco; Miniero Roberto (BMC, 2012)
Abstract Objective The use of complementary and alternative medicine (CAM) has not been widely studied among children in Italy. ISTAT-2005 survey showed a prevalence of 10% concerning children treated with CAM. The lack of data about the use of CAM in pediatrics in the South of Italy aimed us to conduct an epidemiological inquiry in Calabria. Methods The study has been conducted from 2009 and 2011 at the Pediatric Units of: University "Magna Graecia"- Catanzaro (CZ), Pugliese-Ciaccio Hospital-Catanzaro (CZ), Annunziata Hospital-Cosenza (CS), Jazzolino Hospital- ViboValentia (VV), Riuniti Hospitals- Reggio Calabria (RC) and San Giovanni di Dio Hospital- Crotone (KR). All information was collected through a questionnaire proposed to children's parents admitted to these hospitals as out-patients or in-patients. Results 1387 parents were approached to complete the questionnaire. 21(1,5%) refused to answer. A total of 1366 questionnaire was analyzed: 378 at CZ , 450 at CS, 131 at KR, 201 at VV and 206 at RC, with a response rate of 98,5%. In total, the percentage of children using CAM varied from 18% in Crotone to 38% in Cosenza. The parents who used CAM for their children were older and with a higher education. Phytotherapy was preferred to homeopathy. The gastrointestinal pathologies and upper respiratory tract are those ones for which frequently parents recur to CAM. Of note we have not to disregard their use " to strengthen" the immune system. In most of cases CAM have been prescribed by pediatrician. Conclusions Our study remarks that the use of CAM is increased dramatically among the calabrian children in the last years as well as in other countries. Pediatricians need to improve their knowledge about CAM in order to better manage the parental attitude.